The Implementation of Empathy Regulation in Children at Islamic Early Childhood Education Institutions - Devinta, Lawrence Zada’anis; Ernawati, Sri; Riskiana, Dhian (Early Childhood Research Journal (ECRJ), 2025)
Empathy is a crucial aspect that should be nurtured from an early age as a foundation for character development and children’s socialization skills. This study aims to identify the implementation of empathy regulation in children aged 2–4 years at Islamic educational institutions, specifically at KBIT RA Alif Smart Surakarta. The research focuses on four forms of empathy: emotional, cognitive, reflective, and pro-social, as demonstrated by the children toward their peers and teaching staff (ustadzah). This study employs a qualitative descriptive method, involving 7 participants teachers (ustadzah) from KBIT RA Alif Smart with an age range of 20 – 49 years. The findings indicate that most children have developed strong empathetic abilities across all four aspects. Children’s empathetic behaviors are reflected in their ability to imitate the empathetic actions of peers, learn through the exemplary conduct of their teachers, and take personal initiative in showing care for others. The study concludes that empathy regulation at KBIT RA Alif Smart has been effectively implemented through approaches that align with the developmental stages of early childhood.